Best Practice in Systemic Therapy for Head and Neck Squamous Cell Carcinoma - Oosting, Sjoukje F.; Haddad, Robert I. (Frontiers in Oncology, 2019)
Treating head and neck cancer patients with systemic therapy is challenging because of tumor related, patient related and treatment related factors. In this review, we aim to summarize the current standard of care in the curative and palliative setting, and to describe best practice with regard to structural requirements, procedures and monitoring outcome. Treatment advice for individual head and neck cancer patients should be discussed within a multidisciplinary team. Cisplatin is the drug of choice for concomitant chemoradiotherapy in the primary and postoperative setting, and also a main component of induction chemotherapy. However, acute and late toxicity is often significant. Checkpoint inhibitors have recently been proven to be active in the metastatic setting which has resulted in a shift of paradigm. Detailed knowledge, institution of preventive measures, early recognition and prompt treatment of adverse events during systemic therapy is of paramount importance. Documentation of patient characteristics, tumor characteristics, treatment details and clinical and patient reported outcome is essential for monitoring the quality of care. Participation in initiatives for accreditation and registries for benchmarking institutional results are powerful incentives for implementation of best practice procedures.